Battle in Bon Village - Ida Bagus Astika Pidada; Ida Ayu Iran Adhiti; Ida Ayu Pristina Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
On August 17th, 1945, in the name of the Indonesian nation, IR. Sukarno, accompanied by Drs. Mohammad Hatta, proclaimed Indonesian Independence. News of the proclamation was known in Bali on August 23rd, 1945, it was caused by the poor communication and transportation at that time. Although we had achieved independence, Japan in Bali still showed a powerful attitude. To optain weapons, fighters in Bali carried out a general attack on Japanese barracks throughout Bali. This general attack was failed. Furthermore, fighters asked for weapons assistance to Java and reported the situation in Bali. After approximately 3 months in Java, I Gusti Ngurah Rai and his friends returned home to Bali. The area was headed to the village of Munduk Malang in Tabanan regency. From the village of Munduk Malang that the struggle continued by attacking NICA posts around this village. With this attrack, in a short time the position of the fighters was known to NICA. Furthermore, it was decided by I Gusti Ngurah Rai to make a long journey or “Long March”. This jouney started from Bengkel Anyar to Singaraja and continuing to the east. On this journey the fighters carried out attacks in Bon village on June, 13th 1946 in North Badung village.